Comparison of center of pressure and kinematic differences in grand plié with and without the barre - Greenwell, R.; Wilson, M.; Deckert, J.L.; Critchley, M.; Keener, M.; Dai, B. (Journal of Dance Medicine & Science, 2020)
The purpose of this study was to determine what differences exist when performing grand plié with and without the barre. Differences in center of pressure (COP) sway, trunk kinematics, and lower extremity kinematics were used in this analysis for both first (P1) and fifth positions (P5). It was hypothesized that use of the barre would result in decreased COP sway, but increased asymmetries in trunk and lower extremity kinematics would be seen compared with the same movements performed without the barre in both positions. Sixteen collegiate dancers (1 male, 15 female) performed three trials of grand plié in P1 and P5 (right leg crossed in front) with or without the barre, for a total of 12 trials. For the barre condition (BC), participants demonstrated less time to complete grand plié, slightly less depth in grand plié, and decreased anterior-posterior (AP) sway compared to the without barre condition (WBC). The BC condition showed increased peak left trunk rotation, right knee flexion, decreased right and left peak hip flexion, and increased right hip abduction in both P1 and P5. Comparing P1 to P5, there was decreased AP sway, decreased peak left trunk rotation, decreased peak right and left hip flexion, increased left hip abduction, and decreased right knee flexion in both BC and WBC conditions. For the BC, there was increased right hip abduction in P1 compared to P5. Our results indicate that while use of the barre provides proprioceptive information, which helps dancers to control balance and learn a motor control strategy, grand plié should also be taught without the barre to challenge the dancers balance control with different movement patterns in space.